Study on Characteristics of Oil Palm Empty Fruit Bunch to Predict Condensation Temperature of Tar From Its Pyrolysis Gas - Joni Joni; Armansyah Halomoan Tambunan; Radite Praeko Agus Setiawan; Kiman Siregar (International Journal of Oil Palm, 2019)
Palm oil is one type of plants that has various advantages. One of the advantages is almost all parts of the plant, such as trunk, empty fruit bunch (EFB), and the extracted oil, can be utilized as energy. Utilization of EFB for energy, especially the use of combustible gas as direct feed of combustion engines to generate electricity is still rarely used. This is related to the water content and the large amount of volatile substances that will give an unfavorable impact on the quality of the gas produced. To overcome this, information on the characteristics and thermophysical properties, such as dew point, of gases from the EFB biomass is indispensable. In this study, three EFB samples were taken from three different environmental conditions, namely samples A, B and C, to be analyzed. The elemental and proximate analysis as well as GCMS pyrolysis test of the samples were then used to characterize the EFB and determine its thermo-physical properties in terms of its dew point. The elemental analysis of the EFB samples showed disparity of its content, which was around 52.08 ± 7.59% (C), 7.05 ± 0.53% (H), 2.28 ± 0.43% (N), 0.35 ± 0.36% (S) and 34.84 ± 4.45% (O). Likewise, the proximate analysis showed differences around 4.49 ± 2.60% (MC), 5.80 ± 1.97% (FC) and 73.44 ± 3.78% (VM). From the elemental and proximate analysis, it can be predicted that tar compounds produced from pyrolysis of the EFB at a temperature of 400oC, was in the form of mixed oxidation compounds (mixed oxygenates). The compounds were classified as the first tar compound (class 2) consisting of phenols (ketones, phenol and guaiacol). The condensation temperature and the concentration of the tar in its pyrolysis gas were predicted to be 204.22oC, tar 1720.79 mg/Nm3 (sample A); 256.02oC, tar 92.97 mg/Nm3 (sample B); and154.85oC, tar 359.02 mg/Nm3 (sample C), respectively. This information can be useful in designing the tar elimination devices from the pyrolysis gas.